Microplastics from effluents of sewage treatment works and stormwater discharging into the Victoria Harbor, Hong Kong. (August 2020) - Mak, Chu Wa; Tsang, Yiu Yuen; Leung, Matthew Ming-Lok; Fang, James Kar-Hei; Chan, King Ming
Abstract: Sewage treatment works and stormwater outfalls were identified as sources of microplastics in the Victoria Harbor, Hong Kong. Local treated sewage and stormwater effluents contained up to 10, 816 pieces per m 3 of microplastics, mainly polyethylene (PE) and polypropylene (PP), being discharged at an average rate of 3.5 mg per capita daily. Bioaccumulation of microplastics in marine fish collected from the vicinity of the effluent discharge outfalls was also studied. The temporal variations of microplastics in terms of abundance, shape and polymer type in fish were found consistent with those in the effluents and surface water. The abundance of microplastics was significantly higher in March 2017 (dry season). Microplastics in fish were predominantly in fiber form and identified as PE and PP. The observed temporal variations suggest uptake of microplastics by fish from the treated sewage and stormwater effluents. Graphical abstract: Unlabelled Image Highlights: Microplastics (MPs) are abundant in sewage and stormwater effluents in Hong Kong and peak in March. Similar temporal patterns of MPs were confirmed in surface seawater and fish. Polyethylene and polypropylene were the predominant MPs found. Fish near to discharges was found moderately contaminated with MPs. Amount of microplastics found in fish positively correlated with the sizes of fish.